The Effect of Nanoparticles on Mice Brain Tissue: Dampak Nanopartikel terhadap Struktur Jaringan Otak Tikus - Ali, Wasfi Dhahir Abid (Academia Open, 2025)
Nanoparticles (NPs) have attracted considerable attention in biomedical research due to their unique physicochemical properties and potential applications. Cerium oxide (CeO₂) nanoparticles, in particular, have shown promise for their antioxidant and neuroprotective properties. However, concerns remain regarding their safety and potential neurotoxicity, especially with long-term or high-dose exposure. Although research into their biomedical use is expanding, limited in vivo evidence exists on how cerium oxide nanoparticles affect brain tissue at the histological level. This study aimed to examine the histopathological impact of intraperitoneally administered cerium oxide nanoparticles in Mus musculus mice over four weeks. Mice were divided into two groups: one received 1 mL of physiological saline (control), and the other received 1 mL of a solution containing 3.75 µL of cerium oxide daily. After treatment, brain tissues were analyzed histologically. The treated group showed notable alterations in white matter, neurofibers, and glial cells, including glial cell aggregation, necrosis, and degeneration of white matter. These findings provide direct in vivo evidence of potential neurotoxic effects caused by cerium oxide nanoparticles. The study highlights the importance of careful dose regulation and calls for more research into their mechanisms of toxicity and long-term effects to ensure safe biomedical application. Highlight: Cerium oxide nanoparticles caused brain tissue damage in mice. Key effects included glial cell necrosis and white matter degeneration. Highlights need for safe dosing and long-term toxicity studies. Keyword: Rabbits, Nanoparticles, Brain, Tissue, Damage